New Insights into Clostridium difficile (CD) Infection in Latin America: Novel Description of Toxigenic Profiles of Diarrhea-Associated to CD in Bogotá, Colombia - Muñoz, Marina; Ríos-Chaparro, Dora I.; Herrera, Giovanny; Soto-De Leon, Sara C.; Birchenall, Claudia; Pinilla, Darío; Pardo-Oviedo, Juan M.; Josa, Diego F.; Patarroyo, Manuel A.; Ramírez, Juan D. (Frontiers in Microbiology, 2018)
Clostridium difficile (CD) produces antibiotic associated diarrhea and leads to a broad range of diseases. The source of CD infection (CDI) acquisition and toxigenic profile are factors determining the impact of CD. This study aimed at detecting healthcare facility onset- (HCFO) and community-onset (CO) CDI and describing their toxigenic profiles in Bogotá, Colombia. A total of 217 fecal samples from patients suffering diarrhea were simultaneously submitted to two CDI detection strategies: i) in vitro culture using selective chromogenic medium (SCM; chromID, bioMérieux), followed by verification by colony screening (VCS), and ii) molecular detection targeting constitutive genes, using two conventional PCR tests (conv.PCR) (conv.16S y conv.gdh) and a quantitative type of test (qPCR.16s). The CD toxigenic profile identified by any molecular test was described using 6 tests independently for describing PaLoc and CdtLoc organization. High overall CDI frequencies were found by both SCM (52.1%) and conv.PCR (45.6% for conv.16S and 42.4% for conv.gdh), compared to reductions of up to half the frequency by VCS (27.2%) or qPCR.16S (22.6%). Infection frequencies were higher for SCM and conv.16S regarding HCFO but greater for CO concerning conv.gdh, such differences being statistically significant. Heterogeneous toxigenic profiles were found, including amplification with lok1/3 primers simultaneously with other PaLoc markers (tcdA, tcdB or tcdC). These findings correspond the first report regarding the differential detection of CDI using in vitro culture and molecular detection tests in Colombia, the circulation of CD having heterogeneous toxigenic profiles and molecular arrays which could affect the impact of CDI epidemiology.